A look back at an ongoing problem: Shigella dysenteriae type 1 epidemics in refugee settings in Central Africa (1993-1995). - Solen Kernéis; Philippe J Guerin; Lorenz von Seidlein; Dominique Legros; Rebecca F Grais (PLoS ONE)
Background Shigella dysenteriae type 1 (Sd1) is a cause of major dysentery outbreaks, particularly among children and displaced populations in tropical countries. Although outbreaks continue, the characteristics of such outbreaks have rarely been documented. Here, we describe the Sd1 outbreaks occurring between 1993 and 1995 in 11 refugee settlements in Rwanda, Tanzania and Democratic Republic of the Congo (DRC). We also explored the links between the different types of the camps and the magnitude of the outbreaks. Methodology/principal findings Number of cases of bloody diarrhea and deaths were collected on a weekly basis in 11 refugee camps, and analyzed retrospectively. Between November 1993 and February 1995, 181,921 cases of bloody diarrhea were reported. Attack rates ranged from 6.3% to 39.1% and case fatality ratios (CFRs) from 1.5% to 9.0% (available for 5 camps). The CFRs were higher in children under age 5. In Tanzania where the response was rapidly deployed, the mean attack rate was lower than in camps in the region of Goma without an immediate response (13.3% versus 32.1% respectively). Conclusions/significance This description, and the areas where data is missing, highlight both the importance of collecting data in future epidemics, difficulties in documenting outbreaks occurring in complex emergencies and most importantly, the need to assure that minimal requirements are met.